ANALYSIS OF MATHEMATICAL MODEL OF BORING PUMP OPERATION PROCESS - Іващенко, Василь Трифонович; Лях, Михайло Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The recent mathematical model of boring pump operation process is observed in the issue. It subscribe operation modes in boring pumps as: bore washing out process intaking line, simultaneous process intaking line and pump chamber, in pump chamber and discharge line, liquid mud flowing in discharge line. Opportunities for further correction and improving of the mode are investigated, according to results of mathematical model analysis.